2020
DOI: 10.24191/ji.v15i2.352
|View full text |Cite
|
Sign up to set email alerts
|

Issues on Job Mobility in Restaurant Industry: Study on Salary, Work Environment and Promotions

Abstract: Employees are known as an asset to an organization where success or failure of an organizational’ as determinant closely to them.  According to the Department of Statistics Malaysia (2017), there are 891,616 employees working in restaurants in the year 2015.  The Statistic also shows that staff mobility drastically increases every year and this scenario has been debated among hospitality players.  The focus of this study is to discern about issues of job mobility that occur in the restaurant industry in relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…In addition, the managers in this research also mentioned that salary and other benefits are the basic motivators for job hopping behaviour (Human Resources Online, 2018). Finding of this research parallel with study done by Zainol, Abdullah, Rozali, Bahari, and Kamal (2020) which stated salary factor formed the major intent for job mobility crisis in the restaurant industry. This research also discovered employee's career growth as reason to job hop.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, the managers in this research also mentioned that salary and other benefits are the basic motivators for job hopping behaviour (Human Resources Online, 2018). Finding of this research parallel with study done by Zainol, Abdullah, Rozali, Bahari, and Kamal (2020) which stated salary factor formed the major intent for job mobility crisis in the restaurant industry. This research also discovered employee's career growth as reason to job hop.…”
Section: Discussionsupporting
confidence: 71%
“…When employers promoting decisions are fair in the eyes of employees it will increase their commitment level and reduce the turnover intentions. Meanwhile, Zainol et al, (2020) conducted a study in the restaurant industry and found that employees' satisfaction is significantly related to promotions, which might cause employees to have turnover intentions. For instance, employees dissatisfied with the employer's decisions on promotions; it will decrease their commitment or even having an intention to quit the job.…”
Section: Promotions On Turnover Ratementioning
confidence: 99%